The Untranslatable: Challenges in Rendering Hindi Plays into English - Dr. Dipti Ranjan Maharana; Gourika Sharma (Darul Ilmi Bina Insan Foundation, 2025)
This study delves into the challenges of translating culturally nuanced elements in literature, with a focus on untranslatable terms and concepts. Drawing from Indian drama, it explores how cultural idioms, metaphors, and philosophical constructs like rasa and dharma resist direct translation, necessitating innovative strategies to preserve their essence. Employing theories by eminent theorists and translators such as Lawrence Venuti and Sujit Mukherjee, the paper examines the effectiveness of domestication and foreignization in addressing these challenges. It highlights how translators navigate the delicate balance between retaining the cultural integrity of the source text and ensuring accessibility for the target audience. By analyzing case studies and existing translations, this research emphasizes the translator’s role as both an artist and a cultural mediator. The findings underline the significance of cultural sensitivity in translation, advocating for adaptive strategies that respect the original work's aesthetic and cultural dimensions while engaging global readers. This paper contributes to the broader discourse on translation studies, offering insights into the complexities and possibilities of translating culturally rich texts